The convergent neuroscience of Christian prayer and attachment relationships in the context of mental health: a systematic review - Haverkamp, Egbert; Olsman, Erik; Ćurčić-Blake, Branislava; Vila Ramírez, Víctor; Aleman, André; Ket, Johannes C. F.; Schaap-Jonker, Hanneke (Frontiers in Psychology, 2025)
BackgroundIt has become increasingly accepted within psychotherapy to incorporate various forms of spirituality and religiosity to address the rising prevalence of mental health issues. This is well-founded, as a growing number of findings report benefits of spiritual practices for individuals experiencing depression, anxiety, and stress. However, science-based guidelines on how to embed spiritual practices in therapeutic interventions have not been developed, as the mechanisms by which human cognition, spirituality, and mental health interact—positively or negatively—remain largely unknown. Considering one of the most widely practiced religious behaviors worldwide, prayer, it is posited that the experience of interacting with God is psychologically comparable to human attachment bonds that are strongly associated with mental health.MethodThis systematic review assesses the attachment to God hypothesis by providing an overview of the neural regions implicated in Christian prayer and attachment relationships, exploring their potential convergence. A systematic search was conducted in eight databases, resulting in 44 included records that examine brain activity during prayer or the activation of the attachment system in adults.ResultsEvidence was found for convergence between prayer and neural correlates associated with the mentalizing module of attachment, comprising the default mode network (DMN) and areas associated with theory of mind (ToM), both related to social cognition. No significant differences were observed between prayer and attachment in regions connected to the approach and emotion (self-)regulation modules of attachment, whereas findings diverged for the aversion module of attachment, particularly in the insula.DiscussionThe findings highlight shared cognitive and affective dimensions of attachment and prayer. Future research is warranted to identify whether neural patterns observed in different attachment styles coincide with distinct neural patterns of (Christian) prayer, so that both positive and negative effects of prayer can be better understood and integrated into psychotherapy.Systematic review registrationhttps://doi.org/10.17605/OSF.IO/HYZPN.